Mengenal Bahaya Judi Online dan Pinjaman Online pada Seminar dan Penutupan Kuliah Kerja Nyata di Kelurahan Bantar Gebang Bekasi - Sunita Dasman (Jurnal Pelita Pengabdian, 2026)
The seminar “Understanding the Dangers of Online Gambling and Online Loans”, held as part of the Community Service Program (KKN) in Bantar Gebang Subdistrict, Bekasi, aimed to provide education and raise public awareness of the negative impacts of online gambling practices and the use of illegal online loans. The phenomenon of online gambling has become increasingly widespread in society, especially among the younger generation, posing risks of financial losses, addiction, and social problems. Meanwhile, illegal online loans often offer easy access but burden borrowers with high interest rates and distressing debt collection practices. Through this seminar, participants gained an understanding of the risks, prevention mechanisms, and alternative financial solutions that are healthier and more responsible. This activity is expected to improve the community’s digital and financial literacy, helping them avoid harmful practices and fostering a safer, wiser, and more empowered social environment.